Looking Inside the Out-of-Hours Primary Care Consultation: General Practitioners' and Researchers' Experiences of Using Video Observations as a Method. Issue 1 (27th September 2019) - Colliers, Annelies; Coenen, Samuel; Remmen, Roy; Philips, Hilde; Anthierens, Sibyl
Video recording primary care consultations is a promising and valuable method to provide rich data on actual patient–doctor interactions. Video recording for research purposes has not yet been used in out-of-hours (OOH) primary care. To obtain a high grade of participation of general practitioners (GPs), a good understanding on how to organize such a study is essential. We performed qualitative research to explore in what way it would be acceptable to GPs to video record their consultations in OOH. We used semistructured interviews with 17 GPs before setting up video observations. Using this input, we then conducted video observations with an evaluation afterward. We reflected back on the video recordings through a written open-ended questionnaire and during face-to-face elicitation interviews with the 21 participating GPs in the video observations. In addition, we share our experiences from a researchers' view, by describing experiences, advantages, and disadvantages of choices made during the video observations. The stakeholders were involved from the beginning of the setup of the study and it was codesigned with them. Taking into account, their suggestions and concerns led to a high level of participation and successful data collection. We learned that most GPs are willing to participate in a video observation study as they think it could be educational for themselves and research. Nevertheless, because their personal identity is often intertwined with their job as a GP, they feel a bit exposed to criticism but at the same time they are willing to overcome this fear for the purpose of the study. There is also a fear of being judged against a standard way of consulting. GPs describe certain conditions that must be addressed in order for them to participate such as no extra burden to the workload, discrete camera position, and a safe environment for themselves and patients.